General, regional or local anesthesia for successful radial cephalic arteriovenous fistula. Issue 1 (March 2017) - Shemesh, David; Raikhinstein, Yefim; Goldin, Ilya; Olsha, Oded
Autogenous fistulas and in particular radiocephalic fistulas are recommended as the first vascular access for hemodialysis. Unfortunately, the rates of early failure and non-maturation are very high. For more than a decade, brachial plexus block has been proposed as the anesthesia of choice for fistula creation due to its beneficial sympathectomy-like effect, causing vasodilation and attenuation of spasm. Until recently, there was not a single randomized clinical study supporting this proposition. Because performing regional anesthesia is time-consuming and requires expertise, many surgeons prefer local or general anesthesia for vascular access surgery. However, in August 2016 a randomized clinical trial was published showing that regional anesthesia significantly reduces early failure and improves primary and functional patency at 3 months compared to local anesthesia. The aging of the dialysis population, with their attendant morbidity and increased risk for general anesthesia, makes it clear that regional anesthesia is the recommended approach for fistula creation. The excess time required for this approach will decrease with increasing expertise along the learning curve, and will be compensated by a reduction in time that would otherwise be needed for new access construction due to failure of fistulas constructed under local anesthesia.